Enhancing Access to E-books - Harker, Karen; Sassen, Catherine (Evidence Based Library and Information Practice, 2015)
Abstract Objective – The objective of the study was to determine if summary notes or table of contents notes in catalogue records are associated with the usage of e-books in a large university library. Methods – A retrospective cohort study, analyzing titles from three major collections of e-books was employed. Titles were categorized based on the inclusion of the MARC 505 note (table of contents) or MARC 520 note (summary) in the catalogue record. The usage was based on standardized reports from 2012-2013. The measures of usage were the number of titles used and the number of sections downloaded. Statistical methods used in the analysis included correlations and odd ratios (ORs). The usage measures were stratified by publication year and subject to adjust for the effects of these factors on usage. Results – The analysis indicates that these enhancements to the catalogue record increase usage significantly and notably. The probability of an e-book with one of the catalogue record enhancements being used (as indicated by the OR) was over 80% greater than for titles lacking the enhancements, and nearly twice as high for titles with both features. The differences were greatest among the oldest and the most recently published e-books, and those in science and technology. The differences were least among the e-books published between 1998 and 2007 and those in the humanities and social sciences. Conclusion – Libraries can make their collections more accessible to users by enhancing bibliographic records with summary and table of contents notes, and by advocating for their inclusion in vendor-supplied records.